2010
DOI: 10.1007/s00198-010-1317-z
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and vitamin-D supplementation on bone structural properties in peripubertal female identical twins: a randomised controlled trial

Abstract: Daily supplementation for a period of 6 months was associated with increased trabecular area, trabecular density and strength strain index at the ultra-distal tibia and radius and increased cortical area at tibial mid-shaft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Whereas studies in adult and those in older children corroborate these findings [22, 24, 28, 3234], previous investigations have observed that processes underlying skeletal strength may be most sensitive to mechanical strain at this critical stage [3, 6, 28]. It is estimated that the first three weeks of bone remodelling involve resorption processes, while an additional 12 weeks is necessary to complete deposition of mineral matrix.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Whereas studies in adult and those in older children corroborate these findings [22, 24, 28, 3234], previous investigations have observed that processes underlying skeletal strength may be most sensitive to mechanical strain at this critical stage [3, 6, 28]. It is estimated that the first three weeks of bone remodelling involve resorption processes, while an additional 12 weeks is necessary to complete deposition of mineral matrix.…”
Section: Resultsmentioning
confidence: 85%
“…Physical activity represents an extrinsic factor that impacts both mineral accretion and BMAT, exerting permissive capacity of the growing skeleton to achieve its full genetic potential [24]. In accordance with the consistent reports of the beneficial effects of physical activity on bone deposition in children [2530], we hypothesized that in this moderate-intensity weight-bearing physical activity intervention during a critical period of growth and development would result in augmentation of material properties of bone in terms of mineral deposition and femoral marrow cavity volume.…”
Section: Resultsmentioning
confidence: 99%
“…A randomized controlled vitamin D plus calcium supplementation trial in peripubertal female identical twins (n=20; ages 9 to 13 years) showed a more positive impact on bone outcomes [24]. One of each pair was randomized to receive 800 mg of calcium and 400 IU of cholecalciferol, or placebo for 6 months.…”
Section: Nutrition and Bonementioning
confidence: 99%
“…Prevalence of AN is highest among adolescents; sufficient calcium intake during the second decade of life is critical to maximize skeletal growth during the pubertal growth spurt 4,65 and help decrease fracture risk during adulthood. 66 According recent guidelines from the Institute of Medicine, the recommended dietary allowance per day for calcium is 700 mg for children 1-3 years old; 1,000mg for 4-8 years old; 1,300mg for 9-18 years old; 1,000 for 19-70 years old; and 1,200 for 70 years and older.…”
Section: Treatment Considerationsmentioning
confidence: 99%